If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 + -5x + 7 = 2x + 4 Reorder the terms: -2 + 7 + 8x + -5x = 2x + 4 Combine like terms: -2 + 7 = 5 5 + 8x + -5x = 2x + 4 Combine like terms: 8x + -5x = 3x 5 + 3x = 2x + 4 Reorder the terms: 5 + 3x = 4 + 2x Solving 5 + 3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + 3x + -2x = 4 + 2x + -2x Combine like terms: 3x + -2x = 1x 5 + 1x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + 1x = 4 + 0 5 + 1x = 4 Add '-5' to each side of the equation. 5 + -5 + 1x = 4 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 4 + -5 1x = 4 + -5 Combine like terms: 4 + -5 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 909=6c+111 | | x^2+6x=952 | | 4z-2=2z+2 | | k/2=lna | | 13x^2+78x+117=0 | | 0.6666(x+13)=22 | | -1-7x-x=-23 | | x+2x=82 | | N+32=67 | | 5k-12=k | | -1+8k=79 | | 0.6667(x+13)=22 | | 5(-7x+2)=270 | | 4+21x=2.50 | | -110+8x=30+x | | 625x^4=1000x^3 | | Z-5=-11 | | -32=6x+4x+8 | | -14=2(w-3)-4w | | 6x+10=6x+94 | | (X+3)(x+6)=189 | | x+ywhenx=3 | | 1. 6x+10=6x+94 | | (b^7)^2/7 | | 3m+6=6m-3 | | -67=-(j-(-22)) | | 4(2+7x)=204 | | D=1/2mq | | 1. 4(2+7x)=204 | | -5(x-10)=-36 | | K-3/4=4 | | 1/6k=-2/3 |